Effect of Biochar on Phytoextraction of Persistent Organic Pollutants - Pınar Sevim Elibol (Turkish Journal of Agriculture: Food Science and Technology)
Cucurbita pepo spp. pepo has a unique ability to phytoextract Persistent Organic Pollutants (POPs) such as p,p’-DDE from the contaminated soil to plant compartments. Although the uptake mechanism of the POPs by the plants still remains unknown, p,p’-DDE has been accumulated in the plants grown in the contaminated fields, posing the environmental and human health risks. In this study, p,p’-DDE accumulation was investigated in the plants grown in contaminated soils amended with of 0%(control), 0.1%, 1%, and 10% of biochar produced from activated sludge under greenhouse conditions. The p,p’-DDE concentrations in soil and plant samples were measured by an Agilent 7890A GC with μ-ECD detector. The p,p’-DDE concentrations in roots and shoots of the plants were decreased 94% and 87% compared to the control set, respectively by 10 % biochar amendments which are significantly different from the other sets. On the other hand, p,p’-DDE concentrations in roots were not affected by biochar amendments and measured between 7 ng/g to 8 ng/g for the all sets. Biochar from activated sludge will help sustainable usage of the sludge as soil amendments to the contaminated fields, highlighting the importance of some future studies on the products from waste materials.